2019
DOI: 10.7554/elife.42762
|View full text |Cite
|
Sign up to set email alerts
|

Late developing cardiac lymphatic vasculature supports adult zebrafish heart function and regeneration

Abstract: The cardiac lymphatic vascular system and its potentially critical functions in heart patients have been largely underappreciated, in part due to a lack of experimentally accessible systems. We here demonstrate that cardiac lymphatic vessels develop in young adult zebrafish, using coronary arteries to guide their expansion down the ventricle. Mechanistically, we show that in cxcr4a mutants with defective coronary artery development, cardiac lymphatic vessels fail to expand onto the ventricle. In regenerating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(121 citation statements)
references
References 61 publications
5
109
1
3
Order By: Relevance
“…As described above, Folkman and others observed how a tumor, similar to an aberrantly growing organ, draws in a vascular supply, but it is now becoming clear that growing cancers can also become innervated (176) and, just as in a wound, this innervation could be a source of growth signals and, thus, a potential target for anticancer therapeutics. And conversely, although there is a considerable body of literature on the development of cancer lymphatics because of their being a route for cancer cell dissemination (177), only recently have they been investigated in repair scenarios, with the first studies being in the regenerating heart of zebrafish (178). Nerves and lymphatics could both prove to be much more important than currently presumed for wound healing and for cancer biology.…”
Section: Lessons From Cancer For Wound Healing and Vice Versa Now Anmentioning
confidence: 99%
“…As described above, Folkman and others observed how a tumor, similar to an aberrantly growing organ, draws in a vascular supply, but it is now becoming clear that growing cancers can also become innervated (176) and, just as in a wound, this innervation could be a source of growth signals and, thus, a potential target for anticancer therapeutics. And conversely, although there is a considerable body of literature on the development of cancer lymphatics because of their being a route for cancer cell dissemination (177), only recently have they been investigated in repair scenarios, with the first studies being in the regenerating heart of zebrafish (178). Nerves and lymphatics could both prove to be much more important than currently presumed for wound healing and for cancer biology.…”
Section: Lessons From Cancer For Wound Healing and Vice Versa Now Anmentioning
confidence: 99%
“…In mouse embryos, venous derived lymphatics were shown to give rise to the vessels paralleling the coronaries, while non-venous, Tie2-negative yolk sac derived progenitors (Klotz et al, 2015) contribute to the formation of PROX1+ LECs in the developing heart. Recently, three independent studies (Gancz et al, 2019b;Harrison et al, 2019;Vivien et al, 2019) described the development of cardiac lymphatics in zebrafish as well as their role during cardiac regeneration. Interestingly, in addition to conventional lymphatic vessels spanning the cardiac ventricle, Gancz et al (2019b) reported the presence of isolated prox1+, lyve1b+, mrc1+ and flt4+ LEC clusters in the zebrafish heart that developed initially into single capillaries, and later on connected to the existing lymphatic plexus.…”
Section: The Origins Of Lymphatics Endothelial Cellsmentioning
confidence: 99%
“…While live imaging of trunk vascular formation in zebrafish has pioneered our understanding of EC dynamics during development, studies in other vascular beds, particularly late forming vessels have been limited. Recent work has uncovered unique cellular and molecular mechanisms required for development of intestinal vessels (Hen et al, 2015;Goi and Childs, 2016;Koenig et al, 2016), coronary vessels (Harrison et al, 2015;Ivins et al, 2015;Gancz et al, 2019;Harrison et al, 2019;Vivien et al, 2019), caudal vessels (Fukuhara et al, 2014;Goetz et al, 2014;Karthik et al, 2018) and the CCV (Helker et al, 2013) among others. Here, we highlight a few recent studies revealing heterogeneity in cellular mechanisms.…”
Section: Heterogeneity In Cellular Mechanisms In Zebrafish Vascular Dmentioning
confidence: 99%